Antioxidant and Immunomodulatory Activities of Polysaccharides from Fermented Wheat Products of Grifola frondosa: In Vitro Methods - Xiaoqing Xu; Ying Liu; Chunli Pan; Shaoliang Han; Lan Ma; Yu Qiao; Bo Shi; Qing Peng (International Journal of Food Science)
Despite the well-known health benefits of Grifola frondosa, there is a lack of understanding regarding the potential antioxidant and immunomodulatory properties of different varieties when fermented with wheat grains. We aimed to explore the potential of G. frondosa-fermented wheat flour as a functional food. Three varieties of G. frondosa (GFA, GFB, and GFC) were fermented with wheat grains for solid-state fermentation. Polysaccharides were extracted and analyzed for total sugar content, monosaccharide composition, Mw profile, antioxidant activity, cytotoxicity, and immunomodulatory properties. Results were evaluated using HPLC, DPPH assay, MTS assay, Griess reagent, and ELISA method. Our study found variations in three different varieties of G. frondosa-fermented wheat polysaccharides. Glucose was the predominant monosaccharide, followed by galactose and mannose. Each variety had a different molecular weight distribution, with GFA-wheat mainly present in fraction II, GFB-wheat in fraction I, and GFC-wheat in fraction III. At a concentration of 1.25 mg/mL, GFA-wheat and GFB-wheat polysaccharides increased DPPH scavenging ability by 76.8% and 58.7%, respectively. The polysaccharides showed no apparent toxic effect and enhanced the production of NO, IL-6, and TNF-α in RAW 246.7 macrophages. GFB-wheat polysaccharides demonstrated remarkable immunomodulatory properties at a concentration of 5 μg/mL. Our study provides a theoretical basis for using G. frondosa in wheat staple agricultural products to improve human health.